Methamphetamine Increases the Proportion of SIV-Infected Microglia/Macrophages, Alters Metabolic Pathways, and Elevates Cell Death Pathways: A Single-Cell Analysis - Meng Niu; Brenda Morsey; Benjamin G. Lamberty; Katy Emanuel; Fang Yu; Rosiris León-Rivera; Joan W. Berman; Peter J. Gaskill; Stephanie M. Matt; Pawel S. Ciborowski; Howard S. Fox (Viruses, 2020)
Both substance use disorder and HIV infection continue to affect many individuals. Both have untoward effects on the brain, and the two conditions often co-exist. In the brain, macrophages and microglia are infectable by HIV, and these cells are also targets for the effects of drugs of abuse, such as the psychostimulant methamphetamine. To determine the interaction of HIV and methamphetamine, we isolated microglia and brain macrophages from SIV-infected rhesus monkeys that were treated with or without methamphetamine. Cells were subjected to single-cell RNA sequencing and results were analyzed by statistical and bioinformatic analysis. In the animals treated with methamphetamine, a significantly increased proportion of the microglia and/or macrophages were infected by SIV. In addition, gene encoding functions in cell death pathways were increased, and the brain-derived neurotropic factor pathway was inhibited. The gene expression patterns in infected cells did not cluster separately from uninfected cells, but clusters comprised of microglia and/or macrophages from methamphetamine-treated animals differed in neuroinflammatory and metabolic pathways from those comprised of cells from untreated animals. Methamphetamine increases CNS infection by SIV and has adverse effects on both infected and uninfected microglia and brain macrophages, highlighting the dual and interacting harms of HIV infection and drug abuse on the brain.